Method for preparing anticorrosive coating for metal hook by adopting in-situ loading method
Prepare anticorrosion coating for metal hooks by in-situ loading method, and use chemical bonds and cross-linked mesh structure to improve the corrosion resistance and adhesion of the coating, solve the problem of insufficient corrosion resistance of metal anticorrosion coatings in the prior art, and extend the metal The service life of the hook.
Patent Information
- Application Number
- CN202411702409.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The corrosion resistance of existing metal anticorrosion coatings is insufficient and cannot effectively meet the performance requirements of metal materials under external damage such as friction wear, environmental corrosion and photoaging.
Prepare anticorrosion coating for metal hooks by in-situ loading method, by adding 3-glycidyl etheroxypropyltrimethoxysilane and bis-(2-methylallyl)cyclooctan-1,5-dimonium to DMF Raw materials such as olefin and titanium tetrachloride form stable chemical bonds and cross-linked network structures, and are uniformly coated on the metal surface with impregnation and lifting.
It significantly improves the corrosion resistance, adhesion and mechanical properties of the coating, extends the service life of the metal hook, and effectively prevents moisture and oxygen from entering through a dense protective layer to prevent corrosion.
Smart Images

Figure 67457E0352674
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal anticorrosion coatings, in particular to a method for preparing an anticorrosion coating for a metal hook by adopting an in-situ loading method. Background Art
[0002] Metal materials are important structural materials and are widely used in various industries. However, in daily use, metal materials often face some inevitable external damages such as friction and wear, environmental corrosion, light-induced aging, mechanical distortion, etc., which reduce their performance and thus fail to meet people's use needs.
[0003] Chinese patent CN118109070A: relates to the field of anti-corrosion coating technology, and discloses a polyaspartic acid ester resin anti-corrosion coating with wide adaptability to substrates, including the following raw materials in proportion by weight: 50-75 parts of maleate, 65-95 parts of polyether amine, 15-30 parts of polyacrylate, 15-25 parts of isocyanate, 5-10 parts of metal oxide nanomaterials, 6-8 parts of rare earth oxide ultrafine powder, 2-5 parts of graphene oxide, 2-5 parts of defoaming agent, 3-6 parts of adhesion promoter, and 5-7 parts of anti-settling agent.
[0004] Chinese patent CN115746649A: belongs to the field of anti-corrosion coating technology, specifically relates to an anti-corrosion coating for metal and its preparation and application. The raw material components and their mass percentages of the anti-corrosion coating for metal are: 80-95% of photocurable coating precursor, 5-20% of nanoparticles; the raw materials of the photocurable coating precursor include a hydrophobic agent, a crosslinking agent and a photoinitiator; the hydrophobic agent is an unsaturated oleic acid ester with multifunctional double bonds; the crosslinking agent is a thiol derivative.
[0005] Chinese patent CN112795262A: discloses a metal anti-rust coating material, which is composed of the following raw materials in parts by weight: 12-18 parts of dispersant, 28-43 parts of defoamer, 1-3 parts of corrosion inhibitor, 180-210 parts of iron red powder, 10-30 parts of zinc phosphate, 75-85 parts of talc, 14-26 parts of anti-settling agent, 360-400 parts of modified silicone acrylic emulsion, 11-22 parts of film-forming aid, 12-20 parts of thickener, and 150-210 parts of distilled water. The preparation method of the above anti-rust paint is also disclosed.
[0006] The corrosion resistance of the anti-corrosion coatings prepared by the above patents and prior art needs to be further improved. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method, and the operating steps are as follows: S1: slowly add 15-25 parts of 3-glycidyloxypropyltrimethoxysilane, 0.003-0.03 parts of bis-(2-methylallyl)cyclooct-1,5-dieneruthenium CAS: 12289-94-0, 0.5-2 parts of diamminetitanium tetrachloride CAS: 15719-81-0, and 0.5-2 parts of ethylenediamine to 200-300 parts of DMF, heat and stir to react, evaporate to remove DMF, then add 100-120 parts of ethyl acetate, stir evenly to obtain product 1; S2: Mix 12-20 parts of ethyl acetate, 8-12 parts of tetraethyl silicate, and 1-3 parts of glacial acetic acid under room temperature and stir to obtain product 2; S3: adding product 2 dropwise to product 1, mixing and stirring at room temperature, standing at room temperature for aging, and drying to obtain an anticorrosive coating; S4: Use the dipping and pulling method to apply the anti-corrosion coating evenly on the metal hook and dry it.
[0008] One of the preferred technical means of the above overall technical solution is that the reaction temperature of S1 is 65-75°C and the reaction time is 40-100min.
[0009] One of the preferred technical means of the above overall technical solution is that the stirring time of S2 is 40-60 minutes.
[0010] One of the preferred technical means of the above overall technical solution is that the stirring time of S3 is 20-30 minutes.
[0011] One of the preferred technical means of the above overall technical solution is that the aging time of S3 is 18-24h.
[0012] One of the preferred technical means of the above overall technical solution is that the drying temperature of S4 is 50-60°C and the drying time is 20-24h.
[0013] One of the preferred technical means of the above-mentioned overall technical solution is that the immersion time of the immersion pulling method is 5-10 minutes, the pulling speed is 80-100 mm / min, the coating interval is 10-15 minutes, and the coating times is 2 times.
[0014] One of the preferred technical means of the above overall technical solution is that the coating thickness is 60-80μm.
[0015] Reaction mechanism 1.3-Glycidyloxypropyltrimethoxysilane GPTMS and diammine titanium tetrachloride amino-epoxy ring-opening addition reaction: The amino group (-NH2) in diammine titanium tetrachloride attacks the epoxy group (-CH(O)CH2) in GPTMS, causing the epoxy ring to open; a new chemical bond is formed to generate a stable addition product.
[0016] The amino group (-NH2) in diamminetitanium tetrachloride attacks the allyl group (-CH2=C(CH3)-) in bis-(2-methylallyl)cycloocta-1,5-dieneruthenium, and a nucleophilic addition reaction occurs; a new chemical bond is formed to generate a stable addition product.
[0017] Technical Effects The present invention discloses a method for preparing an anti-corrosion coating for a metal hook by using an in-situ loading method. Compared with the prior art, the present invention has the following significant effects: 1. Technical effects of introducing titanium tetrachloride complexes: Enhanced corrosion resistance: Titanium tetrachloride complexes can form stable chemical bonds, improving the density and chemical corrosion resistance of the coating.
[0018] Improved adhesion: The adhesion between the coating and the metal surface is enhanced through chemical reaction with the substrate surface.
[0019] Improve mechanical properties: The formed cross-linked network structure improves the hardness and wear resistance of the coating.
[0020] 2. Technical effects of introducing ruthenocene complexes: Enhanced catalytic activity: Ruthenocene complexes have good catalytic activity, which can promote the curing reaction of the coating and improve the performance of the coating.
[0021] Improve stability: Ruthenocene complexes can stabilize other components in the coating and reduce the degradation of the coating during use.
[0022] Improved anti-corrosion performance: By forming a dense protective layer, it effectively blocks moisture and oxygen from entering the metal surface, thereby preventing corrosion.
[0023] Cross-linking: Multiple reaction sites in the titanium tetrachloride complex can form a cross-linked network structure with other molecules in the coating, increasing the density and strength of the coating. Through chemical reactions with the surface of the substrate, a strong chemical bond is formed, improving the adhesion and corrosion resistance of the coating.
[0024] The dense protective layer formed by the ruthenocene complex can effectively isolate the metal surface from corrosion by the external environment and extend the service life of the metal hook.
[0025] By introducing titanium tetrachloride complexes and ruthenocene complexes, the anti-corrosion coating for metal hooks has been significantly improved in terms of corrosion resistance, adhesion and mechanical properties, thereby effectively extending the service life of the metal hooks. DETAILED DESCRIPTION
[0026] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description in combination with embodiments and comparative examples: Corrosion resistance: characterized by current density and resistance; the smaller the current density, the better the corrosion resistance; the larger the resistance, the better the corrosion resistance; current density and resistance are tested by an electrochemical workstation; the workstation is a three-electrode system, in which the platinum electrode is the counter electrode and the sample to be tested is the working electrode (exposed area is 1cm 2 ), the Ag / AgCl electrode filled with saturated KCl was used as the reference electrode, and the corrosion medium was 3.5wt% NaCl solution; before each electrochemical test, the sample was subjected to an open circuit test for half an hour, and then tested again after the initial potential was stabilized; in the potentiodynamic polarization curve test, the scan rate was set to 5mV / s.
[0027] Example 1 A method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method, wherein the operating steps are as follows: S1: Slowly add 15 g of 3-glycidyloxypropyltrimethoxysilane, 0.003 g of bis-(2-methylallyl)cyclooct-1,5-dieneruthenium CAS: 12289-94-0, 0.5 g of diaminetitanium tetrachloride CAS: 15719-81-0, and 0.5 g of ethylenediamine to 200 g of DMF, heat and stir to react, evaporate to remove DMF, add 100 g of ethyl acetate, stir evenly, and obtain product 1; S2: 12 g of ethyl acetate, 8 g of tetraethyl silicate, and 1 g of glacial acetic acid were mixed and stirred at room temperature to obtain product 2; S3: adding product 2 dropwise to product 1, mixing and stirring at room temperature, standing at room temperature for aging, and drying to obtain an anticorrosive coating; S4: Use the dipping and pulling method to apply the anti-corrosion coating evenly on the metal hook and dry it.
[0028] The reaction temperature of S1 is 65°C and the reaction time is 40 minutes.
[0029] The stirring time of S2 is 40 min.
[0030] The stirring time of S3 is 20 min.
[0031] The aging time of S3 is 18h.
[0032] The drying temperature of S4 is 50°C and the drying time is 20 hours.
[0033] The immersion time of the immersion pulling method is 5 minutes, the pulling speed is 80 mm / min, the coating interval is 10 minutes, and the coating times are 2 times.
[0034] The coating film thickness is 60 μm.
[0035] Example 2 A method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method, wherein the operating steps are as follows: S1: Slowly add 18 g of 3-glycidyloxypropyltrimethoxysilane, 0.01 g of bis-(2-methylallyl)cyclooct-1,5-dieneruthenium CAS: 12289-94-0, 1 g of diaminetitanium tetrachloride CAS: 15719-81-0, and 1 g of ethylenediamine to 240 g of DMF, heat and stir to react, evaporate to remove DMF, add 105 g of ethyl acetate, stir evenly, and obtain product 1; S2: 14 g of ethyl acetate, 9 g of tetraethyl silicate, and 2 g of glacial acetic acid were mixed and stirred at room temperature to obtain product 2; S3: adding product 2 dropwise to product 1, mixing and stirring at room temperature, standing at room temperature for aging, and drying to obtain an anticorrosive coating; S4: Use the dipping and pulling method to apply the anti-corrosion coating evenly on the metal hook and dry it.
[0036] The reaction temperature of S1 is 68°C and the reaction time is 60 minutes.
[0037] The stirring time of S2 is 45 min.
[0038] The stirring time of S3 is 25 min.
[0039] The aging time of S3 is 20h.
[0040] The drying temperature of S4 is 55°C and the drying time is 21 hours.
[0041] The immersion time of the immersion pulling method is 6 minutes, the pulling speed is 85 mm / min, the coating interval is 12 minutes, and the coating times are 2 times.
[0042] The coating film thickness is 70 μm.
[0043] Example 3 A method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method, wherein the operating steps are as follows: S1: Slowly add 23 g of 3-glycidyloxypropyltrimethoxysilane, 0.02 g of bis-(2-methylallyl)cyclooctane-1,5-dieneruthenium, 1.5 g of diaminetitanium tetrachloride, and 1.5 g of ethylenediamine to 280 g of DMF, heat and stir to react, evaporate to remove DMF, add 115 g of ethyl acetate, stir evenly, and obtain product 1; S2: 18 g of ethyl acetate, 11 g of tetraethyl silicate, and 2 g of glacial acetic acid were mixed and stirred at room temperature to obtain product 2; S3: adding product 2 dropwise to product 1, mixing and stirring at room temperature, standing at room temperature for aging, and drying to obtain an anticorrosive coating; S4: Use the dipping and pulling method to apply the anti-corrosion coating evenly on the metal hook and dry it.
[0044] The reaction temperature of S1 is 73°C and the reaction time is 80 minutes.
[0045] The stirring time of S2 is 55 min.
[0046] The stirring time of S3 is 25 min.
[0047] The aging time of S3 is 22h.
[0048] The drying temperature of S4 is 55°C and the drying time is 23h.
[0049] The immersion time of the immersion pulling method is 8 minutes, the pulling speed is 95 mm / min, the coating interval is 14 minutes, and the coating times are 2 times.
[0050] The coating film thickness is 70 μm.
[0051] Example 4 A method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method, wherein the operating steps are as follows: S1: Slowly add 25 g of 3-glycidyloxypropyltrimethoxysilane, 0.03 g of bis-(2-methylallyl)cyclooctane-1,5-dieneruthenium CAS: 12289-94-0, 2 g of diamminetitanium tetrachloride CAS: 15719-81-0, and 2 g of ethylenediamine to 300 g of DMF, heat and stir to react, evaporate to remove DMF, add 120 g of ethyl acetate, stir evenly, and obtain product 1; S2: 20 g of ethyl acetate, 12 g of tetraethyl silicate, and 3 g of glacial acetic acid were mixed and stirred at room temperature to obtain product 2; S3: adding product 2 dropwise to product 1, mixing and stirring at room temperature, standing at room temperature for aging, and drying to obtain an anticorrosive coating; S4: Use the dipping and pulling method to apply the anti-corrosion coating evenly on the metal hook and dry it.
[0052] The reaction temperature of S1 is 75°C and the reaction time is 100 min.
[0053] The stirring time of S2 is 60 min.
[0054] The stirring time of S3 is 30 min.
[0055] The aging time of S3 is 24h.
[0056] The drying temperature of S4 is 60°C and the drying time is 24h.
[0057] The immersion time of the immersion pulling method is 10 minutes, the pulling speed is 100 mm / min, the coating interval is 15 minutes, and the coating times are 2 times.
[0058] The coating film thickness is 80 μm.
[0059] Comparative Example 1 The other steps were the same as in Example 1 except that bis-(2-methylallyl)cyclooct-1,5-dieneruthenium and diamminetitanium tetrachloride were not added.
[0060] Comparative Example 2 The other steps were the same as in Example 1 except that bis-(2-methylallyl)cyclooct-1,5-dieneruthenium was not added.
[0061] Comparative Example 3 No diammine titanium tetrachloride was added, and the other steps were the same as in Example 1.
[0062] The test results are shown in Table 1: Table 1 Through the data analysis of the above embodiments and comparative examples, the anti-corrosion coating prepared by the present invention, when tested in a 3.5wt% NaCl solution by an electrochemical workstation, has a small corrosion current density and a low corrosion rate, and has excellent corrosion resistance.
[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method, wherein the operating steps are as follows: S1: slowly add 15-25 parts of 3-glycidyloxypropyltrimethoxysilane, 0.003-0.03 parts of bis-(2-methylallyl)cyclooctane-1,5-dieneruthenium, 0.5-2 parts of diamminetitanium tetrachloride, and 0.5-2 parts of ethylenediamine to 200-300 parts of DMF, heat and stir to react, evaporate to remove DMF, add 100-120 parts of ethyl acetate, stir evenly, and obtain product 1; S2: Mix 12-20 parts of ethyl acetate, 8-12 parts of tetraethyl silicate, and 1-3 parts of glacial acetic acid at room temperature and stir to obtain product 2; S3: adding product 2 dropwise to product 1, mixing and stirring at room temperature, standing at room temperature for aging, and drying to obtain an anticorrosive coating; S4: Use the dipping and pulling method to apply the anti-corrosion coating evenly on the metal hook and dry it.
2. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The reaction temperature of S1 is 65-75°C and the reaction time is 40-100 minutes.
3. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The stirring time of S2 is 40-60min.
4. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The stirring time of S3 is 20-30min.
5. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The aging time of S3 is 18-24h.
6. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The drying temperature of S4 is 50-60°C and the drying time is 20-24h.
7. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The immersion time of the immersion pulling method is 5-10 minutes, the pulling speed is 80-100 mm / min, the coating interval is 10-15 minutes, and the coating times are 2 times.
8. The method for preparing an anti-corrosion coating for a metal hook by an in-situ loading method according to claim 1, characterized in that: The coating film thickness is 60-80 μm.
